A Conversational Implicature Analysis In Oscar Wilde’s Short Story “Happy Prince” - Faizal Risdianto (Register Journal, 2011)
The title of this paper is a conversational implicature analysis on Oscar Wilde’s “Happy Prince”. In this paper, the writer discusses conversational implicature in one of Oscar Wilde’s short stories entitled “Happy Prince”. The objectives of the study are to identify the implicature utterances conveyed by the characters in Oscar Wilde’s “Happy Prince” and to describe the implied meaning uttered by the characters in Oscar Wilde’s “Happy Prince”. In this study, the writer applies qualitative research method. The objects of this study are ten utterances of conversational implicature in Oscar Wilde’s “Happy Prince”. Those conversational implicature are obtained through frequent reading and analysis. This study employed the researcher as the instrument to find adequate and profound data and analyze them. The procedures and steps that have been used in this research are: (1) the provision of data, (2) data classification, (3) and data analysis. In analyzing the data, the writer uses Gricean theory. It is a theory about conversational implicature generated by four maxims. Those are maxim of quantity, maxim of quality, maxim of relation and maxim of manner. Then the last step is (4) the presentation of data analysis. After conducting the research, the writer found ten conversational implicatures in Oscar Wilde’s short story “Happy Prince”. In the short story, there are some variation’s meanings of the conversational implicature used in the short story which closely related to the conversational implicature; they are cooperative, politeness and ironical principle. In Oscar Wilde’s short story “Happy Prince”, there are six maxims of politeness principle, two maxims of cooperative principles and two maxims of ironical principles. Besides that, the reasons of the conversational implicature used in Oscar Wilde’s short story “Happy Prince” are to make us easyly understand the dialogue in the short story conversations and it is aimed at minimizing misunderstanding among the readers and literary critics.Keywords: Conversational Implicature; Maxims; Gricean Theory; Short Story